The importance of sports medicine for the Sochi Games - Steffen, K.; Engebretsen, L. (British Journal of Sports Medicine, 2014)
Many of us winter sport enthusiasts will still remember the last Winter Olympic Games in Vancouver 2010: fantastic organisation and weatherùa real folk festival with street parties up in Whistler and in downtown Vancouver. However, we also remember a high number of injuries and tears of disappointment among athletes in the spectacular snowboard and ski freestyle races at Cypress Mountain specifically. In these cross-disciplines on snow, inspired by motocross, athletes compete in heats of four and race head-to-head at high speed through jumps and obstacles of varying difficulty. The International Olympic Committee (IOC) injury surveillance during the 2010 Olympic Winter Games reported snowboard and freestyle cross as high-risk disciplines, and women were specifically prone. In many cases, these injuries prevented the athlete from further participation in the Olympics. As part of its commitment to supporting the health and performance of athletes and to the continuing professional development of those who care for them, the IOC Medical Commission now offers a postgraduate-level training programme in sports medicine.